The Roles of Islamic Education Teachers Strategy in Embedding Multicultural Values - Arif Anas; Askar Askar; Hamlan Hamlan (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2021)
The objective of the paper is to find out the strategy of Isalamic education teachers in embedding multicultural values at a senior high school in Palu. The study used a qualitative case study method. Data were gathered through direct observation, un-depth interviews with the school’s teachers, and written material analyses. This study found that the teachers of the school embedded multicultural values through humanistic approach in taching and daily school’s interaction. Students were given tolerance understanding to respect religion and ethnicity differences. The curriculum of the school was also redusugned by integrating multicultural values. Intolerance attitudes were strongy prohibited and stric rules to respect each other were imposed. Islamic education teachers were imposed to teached moderate Islamic teachings which respect multicultural values. Radical Islamic views were prohibited to teach in the school. Muslim and non-Muslim students were treated equally regarding their views and beliefs.